Keragaman Karakter Fenotipik Nyamuk Aedes di Daerah Endemis Demam Berdarah di Kalimantan Barat - Kustiati Kustiati; Siti Ifadatin; Syarief Adiansyah (Biocelebes, 2011)
Research on variety of phenotypic characters Aedes mosquito in dengue fever endemic area in West Kalimantan was conducted on July until December 2008. The research site ware fixed according to Stratified Random Sampling Method. The research was conducted by collating the morphological characters based on form, colour and amount of head, thorax and abdomen. Analysis of cluster using PCA (Principal Component Analysis). The inventory result found four species Aedes mosquito that are A. aegypti, A. albopictus, A. polynesiensis, and A. scuttelaris. Based on principal component analysis each mosquito larva, male and female have 9, 18 and 17 characters respectively determind for those four species of Aedes.